Regenerative Virtual Therapy: The Use of Multisensory Technologies and Mindful Attention for Updating the Altered Representations of the Bodily Self - Riva, Giuseppe; Serino, Silvia; Di Lernia, Daniele; Pagnini, Francesco (Frontiers in Systems Neuroscience, 2021)
The term “regenerative medicine” indicates an emerging trend in biomedical sciences that aims at replacing, engineering, or regenerating human cells, tissues, or organs to restore or establish normal function. So far, the focus of regenerative medicine has been the physical body. Neuroscience, however, is now suggesting that mental disorders can be broadly characterized by a dysfunction in the way the brain computes and integrates representations of the inner and outer body across time (bodily self-consciousness – BSC). In this perspective, we propose a new kind of clinical intervention - “Regenerative Virtual Therapy” – RVT - which integrates knowledge from different disciplines - from neuroscience to computational psychiatry - to regenerate a distorted or faulty BSC. The main goal of RVT is to use technology-based somatic modification techniques to restructure the maladaptive bodily representations behind a pathological condition. Specifically, starting from a bayesian model of our BSC (Body Matrix), we suggest the use of mindful attention, cognitive reappraisal, and brain stimulation techniques merged with high-rewarding and novel synthetic multisensory bodily experience (i.e., a virtual reality full-body Illusion in sync with an high-variance interoceptive modulation) to rewrite a faulty experience of the body and regenerate the individual’s wellbeing.